Baxdrostat and finerenone: new aldosterone synthase-aldosterone-mineralocorticoid receptor hormonal system inhibitors for the drug treatment of resistant arterial hypertension - O. B. Kuzmin; N. V. Buchneva; V. V. Belyanin; V. V. Zhezha; M. V. Stolbova (Рациональная фармакотерапия в кардиологии)
Resistant arterial hypertension is characterized by failure to control target blood pressure despite long-term use of optimal or maximum tolerated doses of three different antihypertensive drugs, including diuretic. Patients with resistant hypertension are included in a group of people at high risk of cardiovascular and renal complications, including accelerated progression of chronic kidney disease with a more rapid transition to the final stage of the disease. Resistant hypertension is based on a salt-sensitive, volume-dependent form of hypertension, which usually occurs against the background of increased aldosterone production and normal or even decreased renin plasma activity. A key role in its formation is played by an increase of sodium reabsorption in the kidneys, associated with excessive activity of aldosterone-sensitive epithelial sodium channels (ENaC), which control the reabsorption of this ion in the distal segments of the nephron. Its assumed that in this pathological process, in addition to aldosterone, is also involved the small Rho GTFase Rac1 — regulatory G-protein, which can enter into a direct ligand-independent interaction with mineralcorticoid receptors, performing the function of a powerful nonsteroidal activator of the transmission of their intracellular signals. Based on controlled, randomized clinical trials, the optimal fourth drug to overcome resistance in such patients is the steroid mineralcorticoid receptor antagonist spironolactone. However, the inclusion of this drug in antihypertensive therapy not only fails to control blood pressure in a significant proportion of patients with resistant hypertension, but also significantly increases the risk of hyperkalemia, especially in people with impaired renal function. The review presents data on the pharmacodynamics and pharmacokinetics of new inhibitors of aldosterone synthase-aldosterone-mineralocorticoid receptor hormonal system baxdrostat and finerenone, as well as the results of clinical studies assessing the clinical effectiveness and safety profile of these drugs in patients with resistant hypertension.